Relationship Between Proactive Coping and Self-Care Management in Patient with Pulmonary Tuberculosis - Dr. Tintin Sukartini, M.Kes; Febrina Ramadhani S.Kep; Laily Hidayati, M.Kep (Universitas Airlangga, 2017)
Introduction: Patient with pulmonary tuberculosis not only experience physical problems but also face psychosocial problems and it can get worse during the treatment phase that gives impact on patients' self-care. In order to prevent further impacts on patients, proactive coping is needed.  This study was aimed to identify the relationship between proactive coping and self-care management in pulmonary tuberculosis patients. Methods: This study was a cross-sectional research. As many as 105 respondents taken with consecutive sampling technique. The inclusion criteria of respondent were pulmonary tuberculosis patients both in intensive and continuous phase. This research was conducted in three primary public health care center in Surabaya, East Java, Indonesia. The variables were proactive coping that was measured by Proactive Coping Inventory (PCI) and self-care management that was measured by Self-care Management questionnaire. The data was analyzed using Spearman test. Results: This study showed that proactive coping had a positive correlation with self-care management in patients with pulmonary tuberculosis (p= 0.000; r= 0,848). Conclusion: This study shows a strong correlation between the variables, whereas the higher the level of proactive coping, the better the self-care management in pulmonary tuberculosis patients. Further research can find out the factors that influence the proactive coping in pulmonary tuberculosis patients thus can improve the self-care behavior.